Investigating the role of user motivations and satisfaction on Weibo continuance intention - Ma, Chenwei; Syed Zainudin, Sharifah Sofiah; Wan Abas, Wan Anita; Feng, Sijing (Human Resource Management Academic Research Society, 2023)
The fast development of the social networking sites (SNS) has paved the way for the development and growth of social media, including Weibo. Scholars have focused on the behavior of social media users. However, they have insufficiently considered the impact of these motivations on the emotional state of individual users. Investigation of the following questions is important to further understand how users’ satisfaction forms user continuance use intention: (1) what is the impact of motivations on a user’s satisfaction? and (2) how does this satisfaction affect continuance use intention? To navigate this intricate maze, our research synergistically integrates the User and Gratification (U&G) and Expectation Confirmation Theory (ECT), offering a robust theoretical scaffold to delve into the myriad impacts of user motivations on satisfaction and, consequently, on the intention to continue using the platform. Grounded in this conceptual framework, an empirical inquiry was initiated through an online questionnaire targeting Weibo's vibrant user base (n=343). Data was analysed by PLS-SEM. The results show that Weibo users' Cognitive needs (CN), personal integrative needs (PIN), social integrative needs (SIN), escape needs (EN) have a significant positive impact on satisfaction (ST), and ST also has a significant positive impact on continued use intention (CI) has a significant positive impact. The study demonstrates the complex relationship between emotional resonance and technological engagement on platforms such as Weibo. Beyond merely describing user behavior, the study reveals deeper, often underlying emotional currents that influence user loyalty and engagement in the digital realm.